2004
DOI: 10.2166/ws.2004.0062
|View full text |Cite
|
Sign up to set email alerts
|

Watershed sources of disinfection byproduct precursors

Abstract: A series of field and laboratory investigations was conducted aimed at characterizing disinfection byproduct (DBP) precursor levels in the Wachusett Reservoir watershed. Samples were collected from spatial based and storm event sampling campaigns, as well as laboratory leaching experiments. These were analyzed for DOC, TOC and DBP precursors in an effort to characterize the changes in precursor levels and natural organic matter (NOM) character in this watershed. Based on these data, it was proposed that freshl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
50
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 21 publications
9
50
1
Order By: Relevance
“…the ratio of the UV absorbance to the dissolved organic carbon concentration). This value has also been found to be a good indicator for the humic content of the water, which has a higher propensity to form DBPs than the non-humic fraction (Reckhow et al 2004). …”
Section: Organic Matrixmentioning
confidence: 95%
See 1 more Smart Citation
“…the ratio of the UV absorbance to the dissolved organic carbon concentration). This value has also been found to be a good indicator for the humic content of the water, which has a higher propensity to form DBPs than the non-humic fraction (Reckhow et al 2004). …”
Section: Organic Matrixmentioning
confidence: 95%
“…Research has shown algal biomass and extracellular products can act as THM precursor material (Reckhow et al 2004). This is particularly problematic for source waters extracted from eutrophic reservoirs, which can lead to potentially elevated THM concentrations at certain times of the year (Graham et al 1998).…”
Section: Organic Matrixmentioning
confidence: 99%
“…It is reported that DOM initiates photoreactions and that it participates in particle surface and colloid chemistry (Thacker et al 2008). It may produce undesirable substances such as disinfection by-products during water treatment processes (Kitis et al 2001;Reckhow et al 2004).…”
mentioning
confidence: 99%
“…Pre-oxidation with ozone or chlorine dioxide leads to lower yields of THM upon chlorination [4]. Some scientists suggest that controlling DOC at the geographic source may even be the most economical way to control disinfection by-product formation [176,193]. Sometimes, drinking water supplies, primarily from surface waters, are mixed with groundwater reserves in order to dilute DOC concentrations; however, this practice can be counterproductive if the groundwater also contains DOC (or even a high fraction of phenolic compounds).…”
Section: The Impact Of Increased Doc On Drinking Water Supply and Trementioning
confidence: 99%